DIGITAL WAQF TRANSFORMATION AND MSME EMPOWERMENT IN THE PERSPECTIVE OF ISLAMIC ECONOMICS: A SYSTEMATIC LITERATURE REVIEW 2020–2025 - Syahril; Muammar Zulfiqri; Aunurrochim (Academic Bright Collaboration, 2026)
This study examines the transformation of digital waqf and its role in empowering micro, small, and medium enterprises (MSMEs) within the Islamic economics framework, identifying dominant thematic clusters, integration models, and structural barriers shaping digital waqf development during 2020–2025. A Systematic Literature Review (SLR) employing the PRISMA 2020 protocol was conducted across Scopus, Google Scholar, and Sinta databases. Structured Boolean searches yielded 487 initial records, of which 57 peer-reviewed articles met all inclusion criteria. Thematic analysis followed Braun and Clarke's (2006) framework, complemented by bibliometric mapping using VOSviewer. Four thematic clusters were identified: digital waqf and SDGs, innovative instruments (CWLS and CWLD), Islamic fintech integration, and productive waqf-based MSME empowerment. The most effective integration model combines Cash Waqf Linked Deposit (CWLD), Shariah crowdfunding, blockchain infrastructure, and holistic MSME mentoring. Implementation is constrained by five structural challenges: regulatory gaps, low Nazhir digital capacity, insufficient public waqf literacy, unequal technological infrastructure, and unresolved Shariah-technology harmonization. This study provides important implications for both theory and practice in Islamic economics. Theoretically, it advances the integration of digital waqf, Islamic fintech, and MSME empowerment within a unified analytical framework, contributing to the development of Islamic Social Finance 2.0 and the operationalization of maqāṣid al-sharī'ah in the digital era. Practically, the findings offer strategic guidance for policymakers, Islamic financial institutions, and nazhir organizations to strengthen regulatory frameworks, enhance digital capacity, and expand inclusive financing mechanisms for MSMEs through scalable digital waqf models. Additionally, this study highlights the need for multi-stakeholder collaboration to overcome structural barriers and accelerate the transformation of waqf into a sustainable instrument for socio-economic development. This study delivers the most comprehensive English-language SLR on digital waqf and MSME empowerment in the Indonesian context, introducing the original Digital Waqf–Fintech–MSME Empowerment Nexus model.